Clinical Trials Operated in Egypt: Big Data Analysis Study - El-Masry, Ayman (Cybrarians journal, 2024)
Clinical trials are one of the most direction, approached by physicians/researchers in the medical sciences field. Clinicaltrials.gov is one of the most comprehensive databases around the world, in this field. It is including clinical trials going in United States, and outside United States. The website is mentioning that the database or US government is not scientifically responsible for these trials. “The U.S. government does not review or approve the safety and science of all studies listed on this website” Egypt is one of the most important countries in the Middle East, with a long history in medical sciences as well. Provided in clinicaltrials.gov around 10 thousand trials going in Egypt. Goal of this study: In this study the author analyzed the whole trials going in Egypt, to reflect the patterns and elements of these medical trials. Research method: The method I used, is the quantitative analysis method to analyze all patterns of Egyptian clinical trials, such as: • Physicians operated the clinical trial. • Reasons and goals of each clinical trial (such as testing and experimenting a drug or a medication or a new way in treatment or diagnosis) • Organization and affiliation related to responsibility or support for the clinical trial. • Methods used and steps toward reaching a result for a clinical trial. • Starting and processing and ending date of clinical trials. To analyze all the above elements and patterns I analyzed all Egyptian clinical trials available in the database of clinicaltrials.gov to approach the goal of this study, and to reflect the effort and role of Egyptian clinical trials and its core subjects. The total number found for clinical trials operated at Egypt in the clinicaltrials.gov database, was around 10530 (Ten thousand and five hundred and thirty) clinical trials. Conclusions: The study and analysis of the whole clinical trials ran at Egypt, resulted and approached important conclusions, such as: • The most rated subject is “Postoperative Pain” as this is the most condition/subject studied in clinical trials ran in Egypt. • The majority of clinical trials in Egypt, started 1/1/2019. Number of these trials were 129 clinical trials. • The majority of “primary completed date” was December the first, 2023. • Number of trials completed at that date were 64 clinical trials in Egypt. • The majority of “completion date” was December, 2023. • Number of trials completed at that date were 72 clinical trials in Egypt. • The majority of “first posted date” was May, 2023. تعد التجارب السريرية من أهم الأدوات التي يعتمد عليها الأطباء والباحثون في تطوير العلوم الطبية وتحسين الرعاية الصحية. وتعتبر قاعدة البيانات ClinicalTrials.gov واحدة من أكثر المصادر شمولا للمعلومات المتعلقة بالتجارب السريرية على مستوى العالم، حيث تشمل التجارب التي تجرى في الولايات المتحدة وخارجها. وعلى الرغم من ذلك، يوضح الموقع أن الحكومة الأمريكية أو قاعدة البيانات نفسها لا تتحمل المسؤولية العلمية عن صحة وسلامة الدراسات المدرجة. تعتبر مصر من الدول الرائدة في منطقة الشرق الأوسط في مجال الطب، وتتمتع بتاريخ طويل في هذا المجال. يشير موقع ClinicalTrials.gov إلى أن هناك حوالي 10,530 تجربة سريرية تجرى في مصر، مما يعكس النشاط الكبير في مجال البحث الطبي في البلاد. هدف الدراسة تهدف هذه الدراسة إلى تحليل شامل للتجارب السريرية التي تُجرى في مصر، بهدف التعرف على الأنماط والعناصر المميزة لهذه التجارب، بما في ذلك: *الأطباء والمراكز البحثية التي تقوم بتنفيذ هذه التجارب. *أهداف التجارب السريرية، مثل اختبار عقاقير جديدة أو استراتيجيات علاجية مبتكرة. *الجهة التنظيمية أو الداعمة المسؤولة عن التجارب. *الأساليب المتبعة في التجارب والخطوات التي تم اتخاذها للوصول إلى النتائج. *تواريخ بدء ومعالجة واكتمال التجارب. منهجية البحث اعتمدت هذه الدراسة على التحليل الكمي لجميع التجارب السريرية المصرية المدرجة في قاعدة بيانات ClinicalTrials.gov، حيث تم تحليل العوامل التالية: *هوية الأطباء والمراكز البحثية المشاركة. *الغايات والأهداف العلمية لكل تجربة. *الجهات التنظيمية أو الداعمة. *الأساليب والمنهجيات المستخدمة. *التواريخ المهمة المتعلقة ببداية ونهاية التجارب. نتائج الدراسة من خلال تحليل 10,530 تجربة سريرية مدرجة في قاعدة بيانات ClinicalTrials.gov، توصلت الدراسة إلى مجموعة من الاستنتاجات الرئيسية، منها: *"الآلم بعد الجراحة" كان الموضوع الأكثر تكرارًا في التجارب السريرية في مصر، مما يعكس أهمية هذا الموضوع في السياق الطبي المحلي. *كان تاريخ بدء أغلب التجارب السريرية في مصر هو 1 يناير 2019، حيث بلغ عددها 129 تجربة. *تم تحديد 1 ديسمبر 2023 كتاريخ الانتهاء الأولي لأغلب التجارب، حيث أكملت 64 تجربة في هذا التاريخ. *كما اكتملت 72 تجربة سريرية في مصر في نفس التاريخ. *كان تاريخ النشر الأولي لأغلب التجارب هو مايو 2023. الخلاصة توفر هذه الدراسة نظرة معمقة على الأنماط والعناصر الأساسية للتجارب السريرية في مصر، مسلطة الضوء على الجهود الكبيرة المبذولة في هذا المجال. وتوضح النتائج أن هناك اهتماماً كبيراً بقضايا طبية مثل "الألم بعد الجراحة"، بالإضافة إلى توافر بنية تحتية تنظيمية قوية لدعم هذه التجارب. تسهم هذه الدراسة في تعزيز الفهم العام لدور مصر في البحث الطبي وتحديد المجالات التي تحتاج إلى مزيد من الاستكشاف والاهتمام.